Regulations and academic culture of halal dress in Islamic Coastal Java University from the Imam Madhhab perspective - Sholihah, Hidayatus; Faizah, Umi; Mukhlasin, Alfath; A.Zaenurrosyid (Halal Studies and Society, 2025)
This study aims to examine how university regulations and academic culture shape halal dress awareness among female students as an expression of Islamic values within the academic sphere. Halal dressing is conceptualized not merely as adherence to sharia but also a symbol of Islamic identity and academic ethics in Islamic higher education institutions. In this study, a qualitative method was used with a phenomenological and descriptive-analytical approach. Data were obtained through interviews with female students, lecturers, and university administrators, as well as direct observations of dressing culture, and a review of regulatory documents concerning Islamic dress codes. Subsequently, data analysis was conducted through reduction, thematic categorization, and interpretation of the fiqh values of the four major Sunni schools of thought, namely Hanafi, Maliki, Shafi‘i, and Hanbali, to identify the meeting point between Islamic legal norms and modern academic culture. The results showed that halal dress regulations at UIN Walisongo and UNISSULA were inclusive, educational, and morally nurturing rather than coercive. According to Imam al-Shafi‘i and Hanbali, complete covering of the aurat represents honor and obedience to sharia, while the Hanafi and Maliki schools provide room for adaptation to local socio-cultural contexts. The academic culture at both universities reflects a synthesis of piety, professionalism, and freedom of expression within the framework of Islamic ethics. The dress code regulations are normative-educational in nature, integrating sharia-based values with academic ethics to foster an awareness of dressing that is not only halal in a legal sense but also thayyib in a moral sense. The success of the halal dress culture in Islamic coastal Java university is determined by the synergy between regulations, spiritual awareness, cross-madhhab fiqh understanding, and the internalization of maq ¯as. id al-syar¯ı‘ah in academic life. In conclusion, this study contributes to developing a model of Islamic academic culture that is moderate, contextual, and characteristic of Islamic coastal Java university.